2018
DOI: 10.1080/02640414.2018.1555904
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of wrist and hip sedentary behaviour and moderate-to-vigorous physical activity raw acceleration cutpoints in older adults

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
87
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(100 citation statements)
references
References 85 publications
11
87
2
Order By: Relevance
“…Older hospitalized patients are characterized by very low PA levels, and thresholds to de ne PA in this population are rare and differ according to studies. In our study, PA levels were de ned according to Bakrania et al (26), light PA being de ned by an acceleration ≥30 mg, whereas in the study of Lim et al (12), a 1-min mean acceleration ≥12 mg was selected to de ne PA. Thresholds similar to those proposed by Lim et al have been reported in free-living older people (median age ≥65 years) (13,33) and younger (26,34) populations. Still, other thresholds for light PA, developed and validated in laboratory calibration or in free-living populations, are usually ≥40 mg (35)(36)(37)(38).…”
Section: Discussionsupporting
confidence: 84%
“…Older hospitalized patients are characterized by very low PA levels, and thresholds to de ne PA in this population are rare and differ according to studies. In our study, PA levels were de ned according to Bakrania et al (26), light PA being de ned by an acceleration ≥30 mg, whereas in the study of Lim et al (12), a 1-min mean acceleration ≥12 mg was selected to de ne PA. Thresholds similar to those proposed by Lim et al have been reported in free-living older people (median age ≥65 years) (13,33) and younger (26,34) populations. Still, other thresholds for light PA, developed and validated in laboratory calibration or in free-living populations, are usually ≥40 mg (35)(36)(37)(38).…”
Section: Discussionsupporting
confidence: 84%
“…Older hospitalized patients are characterized by very low PA levels, and thresholds to define PA in this population are rare and differ according to studies. In our study, PA levels were defined according to Bakrania et al [26], light PA being defined by an acceleration ≥ 30 mg, whereas in the study of Lim et al [12], a 1-min mean acceleration ≥ 12 mg was selected to define PA. Thresholds similar to those proposed by Lim et al have been reported in free-living older people (median age ≥ 65 years) [13,33] and younger [26,34] populations. Still, other thresholds for light PA, developed and validated in laboratory calibration or in free-living populations, are usually ≥40 mg [35][36][37][38].…”
Section: Physical Activity Levels and Distribution Throughout The Daysupporting
confidence: 85%
“…Modern accelerometers provide high-frequency accelerations (often in G s , 1 G ~ 9.8 m/s 2 ) in three axes. Calibration studies are crucial to derive cut-points that translate accelerations into sedentary time (ST) or PA intensities (e.g., light, moderate-to-vigorous (MVPA)) based on metabolic equivalents of the tasks (METs, the ratio of the energy expended during an activity to the resting metabolic rate) [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, cut-points are protocol specific, being dependent on the accelerometer body attachment site or the activities performed in the calibration study, among others. As such, although a number of cut-points have been derived for older adults [ 5 , 6 , 7 ], different populations and protocols make difficult the application of these cut-points in other samples. The rapid advancement of the PA measurement field in the past decade, mainly driven by the access to accelerometer raw data, has resulted in a myriad of methods to process these data [ 8 ].…”
Section: Introductionmentioning
confidence: 99%